MAHASISWA DALAM CENGKRAMAN POLITICAL PRACTICE (Telaah Partisipasi Politik Mahasiswa Pada Pemilu Serentak 2019) - La Ode Efrianto; La Ode Ramalan; Amos Amos; Wa Ode Lusianai (Journal Publicuho, 2019)
The political practice of students in the 2019 simultaneous elections formed by mobilization carried out by candidates for legislative members from various electoral districts together with the winning team and from the party's elite forms a stimulus so that student political participation is deliberately formed according to the political wishes of the legislative members who carry out mobilization. Mobilization results in political participation arising from students no longer based on conscience. This study aims to Political Participation of Students in 2019 Simultaneous Elections. This study uses a qualitative method. Qualitative research is aimed at describing and analyzing phenomena, events, social activities, attitudes, beliefs, perceptions and human thoughts individually or in groups. The results showed that the students' political practice in the 2019 simultaneous elections formed by the mobilization carried out by legislative candidates from various electoral districts together with the winning teams and from the party's elite formed a stimulus so that student political participation was formed in accordance with the political desires of legislative members who mobilize. Mobilization results in political participation arising from students no longer based on conscience.